2019
DOI: 10.1037/pas0000659
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of malingering detection measures for attention-deficit/hyperactivity disorder.

Abstract: This meta-analysis compares stand-alone and embedded performance and symptom validity tests (PVTs and SVTs) for attention-deficit/hyperactivity disorder (ADHD) malingering detection in college students. Simulation design studies utilizing college student samples were included (k = 11). Analyses consisted of measures designed or previously used for malingering detection. Random-effects models were constructed to provide aggregated weighted effect sizes (Hedges’ g), indicating the difference between genuine ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…A recent meta-analysis for feigned ADHD (Wallace et al, 2019) underscored the challenges of using embedded feigning indicators with an average effect size (Hedges’ g = 0.66) that falls below the current standard for even a moderate effect size (≥0.75). For the two detection strategies that were successfully operationalized, FE feigning indicators varied from moderate to very large, whereas SBCP was very large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis for feigned ADHD (Wallace et al, 2019) underscored the challenges of using embedded feigning indicators with an average effect size (Hedges’ g = 0.66) that falls below the current standard for even a moderate effect size (≥0.75). For the two detection strategies that were successfully operationalized, FE feigning indicators varied from moderate to very large, whereas SBCP was very large.…”
Section: Discussionmentioning
confidence: 99%
“…It also failed to discriminate between the two feigning domains ( d for FCI = 0.88; d for FMD = 0.95). Focusing solely on feigned ADHD, a meta-analysis by Wallace et al (2019) found remarkable differences in both methodological rigor as well as effect sizes.…”
mentioning
confidence: 99%
“…Research indicates that symptom validity tests (SVTs) and performance validity tests (PVTs) are the best available means for detecting invalid symptom presentations on behavior rating scales and inadequate effort in cognitive testing respectively in adult ADHD assessment (Sagar, Miller, & Erdodi, 2017;Tucha et al, 2015;Wallace et al, 2019). Numerous expert clinicians on adult ADHD assessment have recommended the use of SVTs and PVTs as part of a comprehensive adult ADHD assessment (e.g., Bordoff, 2017;Ramsey, 2015;Weyandt & DuPaul, 2013).…”
Section: Diagnostic Issuesmentioning
confidence: 99%
“…Importa também referir que a avaliação da atitude malingering é uma tarefa que é parte da avaliação psicológica, i.e., não partilhamos da opinião de que em determinado tipo de processo/perícia se tente procurar traços e/ou atitudes falsas, mas sim que se tenha presente a necessidade de observar essa possibilidade durante a avaliação a fim de evitar enviesamentos cognitivos como por exemplos enviesamentos de confirmação e/ou ancoragem. O uso de um diagnóstico de atitude malinger observou no passado algumas críticas relativamente à forma como estariam incluídos alguns dos seus critérios em versões anteriores do DSM 30 , promovendo algumas alterações em versões recentes do mesmo manual 31 . As maiores diferenças prendem-se com a forma como a atitude malinger poderá ser interpretada e confundida com a atitude de feigning Profissionais de psicologia forense deverão ter em consideração potenciais enviesamentos cognitivos em momentos de avaliação com os obstáculos que a análise da atitude falsa, nomeadamente da atitude malinger contém 21 .…”
Section: Discussionunclassified